THE IMPACT OF ENTREPRENEURSHIP EDUCATION AND FAMILY SUPPORT TOWARD STUDENT ENTREPRENEURIAL INTENTION - Bataragoa, Trini K.; Massie, James D. D.; Gunawan, Emilia (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Planting entrepreneurial values is very important given to people who live in the 21st century the importance of entrepreneurship for the country it can cover the economic problems that exist in Indonesia. Entrepreneurship is one of the important inputs, in economic development especially in developing countries. The purpose of this research is to analyze the impact of Entrepreneurship Education and Family Support towards Student Entrepreneurial Intention. This research uses a quantitative research method. The data obtained by distributing questionnaires to 100 students of IBA Student of UNSRAT that are completed, entrepreneurship classes. The results of the study were processed using SPSS version 26. The data is analyzed by using multiple regression analysis. The validity test in this research is using Pearson correlation while the reliability in this research is using Cronbach’s Alpha. The findings revealed Entrepreneurship Education has a positive relationship and significant influence on the Student Entrepreneurial Intention, and Family Support have a positive relationship and no significant influence on the Student Entrepreneurial Intention. To be a successful entrepreneur, students need to learn by doing. Which means students have to learn, practice, and implement it into real life because entrepreneurship has a positive effect in order to develop soft skill on entrepreneurial intention. Keywords: entrepreneurship education, family support, entrepreneurial intention